Multi–criteria livestock assessment for sustainability of smallholder farms in Kwa-Zulu Natal - Mahlobo, Busie Truetia (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.